Population Kinetics and Protein Profiles of Co-Cultured Adult and Fetus Rabbit Bladder Smooth Muscle Cells - Hayrunisa Kahraman Esen; Burcu Biltekin; Mevlit Korkmaz; B. Haluk Güvenç (Urology Research and Practice)
Objective: Bladder tissue models have been developed using smooth muscle cells (SMCs) on various scaffolds to mimic bladder morphology and physiology. This study investigates the effects of co-culturing fetal and adult SMCs on growth properties and protein profiles to understand cellular interactions and population kinetics.